Business Strategies for Pest Control Services in Expanding the Retail and Residential Market Segments: A Case Study of PT XYZ - Andriana Kartina Wingtyas; Yudha Heryawan Asnawi; Irvandi Gustari (Pelopor Publikasi Akademika, 2026)
PT XYZ, an Indonesian facility management company, faces a liquidity crisis with its cash ratio below 10% and a declining current ratio (2020–2023). A major client mandates a minimum cash ratio of 10% for tender eligibility; failure would disqualify PT XYZ. This pressure drives the company to expand its pest control unit from B2B (oil and gas, state-owned enterprises) into retail and residential markets, which offer faster accounts receivable turnover. This research aims to map the existing business model using the Business Model Canvas (BMC), analyze internal and external factors, and determine strategic priorities via A'WOT (AHP+SWOT). Data were collected through interviews, observation, and expert questionnaires. The BMC reveals a model heavily reliant on tenders and personal service assistance. A'WOT results show that the top opportunity is Regulation PERMENKES No. 14/2021 (0.274), the key strength is the Termigon brand (0.070), the main threat is lower local prices (0.031), and the primary weakness is a 24-hour response time (0.019). The top strategic priority is Termigon brand differentiation against foreign multinationals and low-priced local competitors (0.170). Managerial implications include strengthening brand positioning, accelerating ERP-based digital reporting, and optimizing response speed.